INNOVATIVE "PROBLEM" TECHNOLOGY IN EDUCATION APPLICATION IN ECOLOGY LESSONS (Scientific journal of the Fergana State University, 2026)
The article describes the importance of using problem situations in entomology lessons, methods and rules for creating problem situations and the use of innovative technologies in the study of insects. The importance of innovative technologies in education is described, which creates new opportunities for learning and the emergence of opportunities for personalizing learning, expanding communication opportunities and creating a more productive environment for learning entomology. It describes regular and systematic work on training, providing instant access to the necessary information and fostering important skills in working with sources, the ability to distinguish high-quality sources of information from unreliable, attracting young people to scientific activities, the formation of an innovative infrastructure of science in higher educational institutions.